Commodity boom and environmental policy: What lies behind the Amazon deforestation - Rodrigo Mendes Pereira (Institute for Applied Economic Research (ipea), 2019)
This paper investigates the apparent paradox of the mid 2000's sharp reduction in the deforestation of the Brazilian Amazon that happened alongside fast growing commodity markets. Particular attention is given to the role played by PPCDAM, an environmental policy introduced by the federal government in 2004. We use a panel of 760 Amazon municipalities and 15 years to estimate the effects of well-known drivers in the deforestation process, such as cattle herd and soybean crops, as well as the effect of the conservation policy. The results suggest that the policy not only had a direct effect of reducing deforestation, but also rendered deforestation less sensitive to fluctuations in the Amazon commodity production. We also perform a counterfactual exercise, estimating the levels of deforestation that would have been registered, had the policy not existed. We estimate that the plan saved a total of 196 thousand square kilometers of forest between 2005 and 2015, corresponding to almost twice the total amount of deforestation observed during this period, and 4.9% of the entire Brazilian Amazon forest.
Keywords: C33; Q50; 330; deforestation; commodity boom; environmental policy; Brazilian Amazon